The role of Community Mobilization in maternal care provision for women in sub-Saharan Africa- A systematic review of studies using an experimental design - Muzyamba, Choolwe (BMC Pregnancy Childbirth, 2017)
BACKGROUND: While the role of community mobilization in improving maternal health outcomes of HIV positive women in sub-Saharan Africa is continuously emphasized, little is known about how legitimate these claims are. The aim of this study is to systematically review the empirical evidence on this issue. METHODS: A systematic search was conducted in PuBMed, Scopus, Web of Science, MEDLINE, COCHRANE, Allied Health Literature, and Cumulative Index to Nursing. RESULTS: Our search identified 14 publications on the role of community mobilization in maternal care provision in sub-Saharan Africa, including both HIV negative women and women with HIV, that have used experimental research designs. Regarding HIV negative women, literature has demonstrated that community mobilization is a useful strategy for promoting both positive maternal process results and maternal health outcomes. Most of the literature on women with HIV has focused only on demonstrating the causal link between community mobilization and process results. There has been very little focus on demonstrating the causal link between community mobilization and maternal outcomes for women living with HIV. Overall, the results show that while there is some empirical evidence on a causal link between community mobilization and maternal health outcomes for HIV negative women, this kind of evidence is still missing for HIV positive women. Moreover, as shown by the studies, community mobilization as a maternal health strategy is still in its infancy. CONCLUSION: Given the gaps identified in our review, we recommend further research with the aim of providing sound evidence on the role of community mobilization in improving maternal health outcomes of women with HIV in sub-Saharan Africa.